A Mini Review: Application Progress of Magnetic Graphene Three-Dimensional Materials for Water Purification - Wang, Biao; Liu, Qingwang; Fan, Zhenzhong (Frontiers in Chemistry, 2020)
Marine oil pollution, colored counterattacks, and heavy metal ions in water can cause serious environmental problems and threaten human health. The three-dimensional material prepared by graphene, as a new nanomaterial, has a large specific surface area and surface chemical activity. Various impurities in water can be absorbed, which is very suitable as a water purification material. Depositing Fe3O4 and other magnetic materials on graphene three-dimensional materials can not only increase recyclability, but increase hydrophobicity. Therefore, magnetic graphene three-dimensional materials have extremely high potential for use in water purification. This article reviews the research progress and adsorption mechanism of magnetic graphene materials for water purification. Finally, the future research prospects of magnetic graphene materials are prospected.